Institutional Analysis of Downstreaming Policies and Indonesia's Political Economic Resilience in Global Geopolitical Fragmentation - Moh. Riziq (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2025)
This study aims to analyse the institutional dynamics underlying changes in Indonesia's political economy and their implications for downstreaming policies and national economic resilience amid increasing global geopolitical fragmentation, including escalating competition between major powers (the United States and China) and trade disputes within the World Trade Organization (WTO). Downstreaming of natural resources is positioned as a strategic instrument to increase domestic economic value, strengthen industrialisation, and improve Indonesia's bargaining position in the global supply chains. This study employs a descriptive qualitative research design, using historical-institutional and policy analysis approaches. Data were obtained from various sources, including regulations related to downstreaming and mineral resources, books, academic publications, government policies, and other relevant sources. The results show that strengthening the role of the state in the management of strategic resources enables the implementation of more offensive downstreaming policies, such as the ban on nickel ore exports, which has triggered increased investment in smelters and significant growth in the basic metal processing industry. Downstreaming has proven to expand the domestic industrial base and contribute to economic resilience. However, the effectiveness of the policy is highly dependent on the quality of the bureaucracy, transparency of governance, and Indonesia's capacity to manage external geopolitical pressures. As a result, downstreaming can serve as a strategic pillar of sustainable economic development, as well as an instrument of national resilience in an increasingly fragmented global era. Keywords: Downstreaming, Political Economy, Economic Resilience, Global Geopolitics JEL: A11, A13